2014
DOI: 10.1002/jbm.b.33093
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of wollastonite‐poly(N‐butyl‐2‐cyanoacrylate) composites

Abstract: Wollastonite-poly(n-butyl-2-cyanoacrylate) composite (W-BCA) has been proposed to immobilize anatomically bone fragments in order to achieve an optimal healing process. The present study evaluated the in vitro and in vivo behavior of three types of fillers: powdered natural wollastonite (Wn), synthetic pseudowollastonite powder (Ws), and synthetic pseudowollastonite powder coated with 5% acetyl tributyl citrate (Wst). The Wst-BCA composite underwent a higher degradability in the real-time degradation test and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
1
8
0
1
Order By: Relevance
“…Recently, the calcium silicate (CaSiO 3 , CS) ceramics and their composites are investigated as potentially new type of bioceramics for bone regeneration and bone tissue engineering applications [2][3][4][5][6][7][8][9][10][11][12][13][14]. Previous studies have confirmed that the CS bioceramics possess excellent bioactivity and biodegradability [12], and in vitro cell culture studies have shown that the CS bioceramics well supported the attachment and proliferation of bone marrow mesenchymal stem cells (BMSCs) and osteoblasts [11,13,15], and the bioactive Si ions released from CS provided a preferable extracellular environment for directing BMSCs proliferation and differentiation toward the osteogenic lineage [9], and enhancing the proliferation and angiogenesis process of the human umbilical vein endothelial cells (HUVECs) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the calcium silicate (CaSiO 3 , CS) ceramics and their composites are investigated as potentially new type of bioceramics for bone regeneration and bone tissue engineering applications [2][3][4][5][6][7][8][9][10][11][12][13][14]. Previous studies have confirmed that the CS bioceramics possess excellent bioactivity and biodegradability [12], and in vitro cell culture studies have shown that the CS bioceramics well supported the attachment and proliferation of bone marrow mesenchymal stem cells (BMSCs) and osteoblasts [11,13,15], and the bioactive Si ions released from CS provided a preferable extracellular environment for directing BMSCs proliferation and differentiation toward the osteogenic lineage [9], and enhancing the proliferation and angiogenesis process of the human umbilical vein endothelial cells (HUVECs) [3].…”
Section: Introductionmentioning
confidence: 99%
“…The tissue adhesive used in the present study is a blend of n-butyl cyanoacrylate and 2-octyl cyanoacrylate and studies that have attempted to evaluate the cytotoxicity of adhesives with similar composition, showed a level of cytotoxicity around 40% [34] 60% [31,35] which is higher than the values found for shorth length alkyl chains [31,34]. In the present study the cell viability was 39.66%, which was similar to ndings of previous reports of similar adhesives, and lower when compared with the ISO 10993-12 speci cation that considers 70% to be the minimum requirement for toxicity in biomedical materials [34].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have described the use of NBCA as a tissue adhesive. NBCA has been used with variable success rates for the treatment of bone fractures, ossicular fixation, embolization, fistulas, and hemostasis of esophageal varices or bleeding gastric ulcers as well as for vascular or tracheal anastomoses [71316171819202122232425]. These remarkable studies attempted to show the potential applications of NBCA.…”
Section: Discussionmentioning
confidence: 99%